3, 3'-Diindolylmethane alleviates acute atopic dermatitis by regulating T cell differentiation in a mouse model. (February 2021) - Wu, Xianxian; Liu, Jinxuan; Chen, Chaoqin; Huang, Zhen; Zang, Yuhui; Chen, Jiangning; Dong, Lei; Zhang, Junfeng; Ding, Zhi
Highlights: 3, 3′-Diindolylmethane may alleviate atopic dermatitis by promoting the differentiation of Treg cells. 3, 3′-Diindolylmethane inhibits the differentiation of Th2 and Th17 cells via binding to the aryl hydrocarbon receptor. 3, 3′-Diindolylmethane reduces the secretion of TSLP in HaCaT cells via inhibiting NF-κB signaling pathway. Abstract: Atopic dermatitis is a severe, chronic relapsing inflammatory disease of the skin with family clustering. It is characterized into acute phase, which is dominated by T helper 2-type immune responses, and chronic phase, which is dominated by T helper 1-type immune responses. Studies have shown that 3, 3′-diindolylmethane not only has antitumor effects but also can relieve symptoms of inflammatory diseases by inhibiting the nuclear factor-κB signaling pathway and regulating T cell differentiation. To study the effect of 3, 3′-diindolylmethane on atopic dermatitis and the underlying mechanism, a mouse model of acute atopic dermatitis was established using 2, 4-dinitrofluorobenzene. After intraperitoneal injection of 3, 3′-diindolylmethane, skin erythema and edema in mice were significantly alleviated. Furthermore, 3, 3′-diindolylmethane reduced immune activation, probably by inhibiting the secretion of thymic stromal lymphopoietin by keratinocytes. 3, 3′-Diindolylmethane also promoted the differentiation of regulatory T cells and inhibited the activation of T helper 2 and T helper 17 cells to reduce atopic dermatitis-related immune responses. However, it showed no significant effect on the differentiation of T helper 1 cells. These results indicate that 3, 3′-diindolylmethane has a significant inhibitory effect on T helper 2 cells in the acute phase of atopic dermatitis. Our findings may provide not only more insights into the pathological mechanism of AD, but also a new candidate medicine for it.